2022
DOI: 10.1002/jpen.2267
|View full text |Cite|
|
Sign up to set email alerts
|

Guidelines for the provision of nutrition support therapy in the adult critically ill patient: The American Society for Parenteral and Enteral Nutrition

Abstract: Background This guideline updates recommendations from the 2016 American Society for Parenteral and Enteral Nutrition (ASPEN)/Society of Critical Care Medicine (SCCM) critical care nutrition guideline for five foundational questions central to critical care nutrition support. Methods The Grading of Recommendations, Assessment, Development and Evaluation (GRADE) process was used to develop and summarize evidence for clinical practice recommendations. Clinical outcomes were assessed for (1) higher vs lower energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
354
3
30

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 331 publications
(396 citation statements)
references
References 42 publications
9
354
3
30
Order By: Relevance
“…(23) Major nutrition societal guidelines recommend initiating EN in patients with circulatory shock after hemodynamic stability and EN initiation beyond 48 hours may be due to greater initial severity of illness. (11,24,25) However, our study found the EEN group had greater baseline severity of illness, including higher mNUTRIC, APACHE II, and SOFA scores. The signi cant delay, beyond the recommended 48 hours, may be due to a paucity of data on the optimal timing of EN initiation in circulatory shock.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…(23) Major nutrition societal guidelines recommend initiating EN in patients with circulatory shock after hemodynamic stability and EN initiation beyond 48 hours may be due to greater initial severity of illness. (11,24,25) However, our study found the EEN group had greater baseline severity of illness, including higher mNUTRIC, APACHE II, and SOFA scores. The signi cant delay, beyond the recommended 48 hours, may be due to a paucity of data on the optimal timing of EN initiation in circulatory shock.…”
Section: Discussionmentioning
confidence: 56%
“…Unlike the recommendation to initiate EEN in the general ICU patient, which is supported by multiple RCTs (that did not include patients with circulatory shock), the evidence base informing timing of EN in circulatory shock consists of pre-clinical and human observational and small RCTs, including a phase II pilot feasibility study demonstrating protocol compliance and safety of early trophic EN in septic shock. 24 Furthermore, critical care nutrition guidelines recommend, based on expert opinion, that EN be withheld until the patient is fully resuscitated and/or stable. (11,26) The de nition of stability is unspeci ed and, therefore, ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative narrative of chief guideline points in pediatric and adult is presented in Table 1 and Table 2 . 4…”
Section: Methodsmentioning
confidence: 99%
“…In early critical illness, research has shown that there is no difference in clinical outcomes in patients that are fed EN vs. PN for short periods of time (5 to 7 days). Thus, PN may be an appropriate substitute should EN not be feasible in this population [ 3 ].…”
Section: Indications/contraindicationsmentioning
confidence: 99%